Helicobacter pylori infection and its impact on metabolic dysfunction-associated steatotic liver disease: a mediation analysis of neutrophil-albumin ratio - He, Liuying; Yang, Haiyan; Zeng, Ziqin; Wang, Qian; Guan, Haitao; Zhao, Ping (Frontiers in Nutrition, 2025)
BackgroundHelicobacter pylori, a widely found bacterium, has been controversially connected to the risk of metabolic dysfunction-associated steatotic liver disease (MASLD). How the neutrophil–albumin ratio (NAR) influences the relationship between H. pylori infection and MASLD is unknown. Therefore, in this study, how H. pylori infection, the NAR, and MASLD are connected, including the possible impact of the NAR on the relationship between H. pylori and MASLD, was investigated.MethodsIn this cross-sectional study, data from 26,245 medical check-ups conducted between January 2021 and August 2023 at a tertiary hospital located in northwestern China were used. H. pylori infection was used as the independent variable, with metabolic dysfunction-associated steatotic liver disease (MASLD) as the dependent variable and the neutrophil–albumin ratio (NAR) as a mediator. The associations between H. pylori infection, the NAR, and the risk of MASLD were evaluated with a logistic regression model, and mediation analysis confirmed the role of the NAR as a mediator.ResultsAmong 26,245 participants, the frequencies of H. pylori infection and MASLD were 30.5 and 25.8%, respectively, and the mean value of NAR was 0.72 ± 0.241. The analysis using multiple logistic regression indicated a link between H. pylori infection and NAR (Q2: OR = 1.293, 95% CI: 1.199–1.396; Q3: OR = 1.364, 95% CI: 1.263–1.472; Q4: OR = 1.517, 95% CI: 1.406–1.638) and MASLD (OR = 1.226, 95% CI: 1.156–1.301). RCS analysis revealed a significant positive non-linear relationship. The mediation effect analysis found that H. pylori directly contributed to MASLD development (β = 0.014, p = 0.004), and NAR partially mediated the indirect effect of H. pylori on MASLD (β = 0.008, p < 0.001), with 35.77% of the effect being mediated.ConclusionThere was a positive correlation between H. pylori infection and MASLD risk, with NAR partially mediating this connection. This study provides clinical evidence elucidating the impact of Helicobacter pylori infection on MASLD.